Prospective case series on home-based handgrip resistance training with WhatsApp monitoring in patients with newly created arteriovenous fistulas - Hidayat, Muhammad Syairozi; Waluyo, Yose; Aritonang, Sylvia Evelyn; Zainuddin, Andi Alfian; Rasyid, Haerani; Kusumanegara, Jayarasti; Usman, Umar; Nuralim, Muhammad Zulfadly (Ukrainian Journal of Nephrology and Dialysis, 2025)
Successful maturation of arteriovenous fistulas (AVFs) remains a challenge for patients with end-stage kidney disease, particularly in resource-limited settings. Handgrip resistance training may enhance vascular hemodynamics and support AVF maturation. This prospective uncontrolled case series evaluated the feasibility, safety, and vascular changes of a four-week home-based handgrip program in patients with new AVFs. Methods. Twenty-eight adults with recent radiocephalic AVF creation performed daily handgrip training for four weeks (three sets of 10 contractions, 10 seconds each with 2-second rests; 3–5 minutes/day). Adherence was tracked via logbooks and weekly WhatsApp submissions. Feasibility outcomes included adherence, completion, safety, and patient acceptability. Hemodynamic parameters (vein diameter, vein depth, and blood flow volume) were measured using Doppler ultrasonography before and after the intervention. Results. Of 28 participants, 23 (82.1%) completed the program with high adherence (≥85% sessions). No AVF-related adverse events occurred. Significant vascular changes were observed: vein diameter increased from 3.1 ± 0.4 mm to 5.5 ± 0.6 mm (p < 0.001), vein depth decreased from 2.5 ± 0.3 mm to 2.1 ± 0.4 mm (p = 0.002), and blood-flow volume increased from 180 ± 55 mL/min to 565 ± 110 mL/min (p < 0.001). Conclusions. Home-based handgrip training with digital monitoring is feasible, safe, and well accepted in patients with new AVFs. The observed vascular changes suggest this low-cost intervention may support AVF maturation and is suitable for integration into dialysis care in resource-limited settings.